Optimum design of thrust air bearing for hard disk drive spindle motor - Ibrahim, M.D; Namba, T.; Ochiai, M.; Hashimoto, H. (The Japan Society of Mechanical Engineers, 2010)
This paper describes the application of geometry optimization method proposed by Hashimoto to the design of air lubricated thrust bearings used for HDD spindle motors. The optimization is carried out to maximize the dynamic stiffness of air films because the low stiffness is a serious problem of thrust air bearings in the actual application to HDD spindle motor. The optimized dynamic stiffnesses are obtained by changing the allowable film thickness, which is corresponding to the tolerance of bearings. The results obtained show that the optimized thrust air bearings have the comparable stiffness to the oil lubricated thrust bearings and it is verified theoretically that this type of thrust air bearing can be used for HDD spindle motors.